Effect of Spirulina platensis suspension on quality and quantity of sperm and expression of caspase-3 of testis in diabetic wistar rats induced by streptozotocin - Ayu Shabrina; Kintoko Kintoko; Sapto Yuliani; Adhi Gunawan (Pharmaciana, 2019)
Diabetes is metabolic disorders caused by oxidative stress that has always been linked to male reproductive dysfunction. Spirulina platensis has been used for therapeutic supplements for diabetes and repairing reproduction organs based on its antioxidant effects. The aim of this study was to examine the effect of Spirulina platensis suspension (SP) on quality and quantity of sperm also the expression of caspase-3 on testis in male Wistar rats induced by streptozotocin (STZ). This study used 30 adult male Wistar rats that divided into 6 groups of K1 (normal), K2 (single injection of STZ 45 mg/kg BW), K3 (normal rats treated with SP 36/kg BW/day) and treatment group K4, K5 and K6 were diabetic rats given with SP 36 mg/kgBW, 72 mg/kgBW and 144 mg/kg BW. The treatment was given orally for 28 days. Blood glucose level levels were measured using the biochemical analyzer. Quality and quantity of sperm were analyzed using Neubauer slide under the microscope. Apoptosis of Leydig cells was detected by immunohistochemical staining using Caspase-3 polyclonal antibodies. The result showed that there were significant differences between groups (p < 0.05) in final blood glucose level, quality, and quantity of spermatozoa and expression of caspase-3. Our findings clearly highlight the role of Spirulina platensis as an antidiabetes and protective agent for reproducton organs of STZ-induced in diabetic male Wistar rats that improves quality and quantity of sperm cells and reproductive organs.